PENGGUNAAN MODEL ELICTING ACTIVITIES (MEAs) DALAM MENINGKATKAN HASIL BELAJAR DITINJAU DARI SELF CONFIDENCE PADA MATERI ARITMATIKA - Maria Fatima Mei; Maria Trisna Sero Wondo; Stefania Baptis Seto; Konstantinus Denny Pareira Meke (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The low learning outcomes and self-confidence of students in making mathematical models based on story problems are caused by the lack of precise learning models used by teachers. The purpose of this study was to determine the effectiveness of MEAs on learning outcomes and self-confidence in grade VII students of SMPK St. Maria Goreti Ende. This research is a quasi-experimental research sample of 20 students of class VII SMPK St. The randomly selected Maria Gorety Ende. The instrument used in this study is a test of learning outcomes and self-confidence. Data collection techniques were carried out using tests and questionnaires. Data analysis was done descriptively and inferentially. The results of the study concluded that the learning outcomes test obtained a significant value of 0.000, which means that the p-value <0.005 and for self-confidence 0.000, it means the p-value <0.005, so a decision can be taken that Ho is rejected, which means that there are differences between the pre-test and post-test. test test of student learning outcomes and self-confidence before and after the use of the eliciting activities model. Therefore, it can be concluded that for the VII students of SMPK St. Maria Gorety after using the eliciting activities model, the learning outcomes and self-confidence became better than before using the eliciting activities model.